Stimuli‐triggered Self‐Assembly of Gold Nanoparticles: Recent Advances in Fabrication and Biomedical Applications - Zhao, Yan; Cui, Chaoxiang; Fan, Guohua; Shi, Haibin (Chemistry, an Asian journal, 2024)
Gold nanoparticles have been widely used in engineering, material chemistry, and biomedical applications owing to their ease of synthesis and functionalization, localized surface plasmon resonance (LSPR), great chemical stability, excellent biocompatibility, tunable optical and electronic property. In recent years, the decoration and modification of gold nanoparticles with small molecules, ligands, surfactants, peptides, DNA/RNA, and proteins have been systematically studied. In this review, we summarize the recent approaches on stimuli‐triggered self‐assembly of gold nanoparticles and introduce the breakthrough of gold nanoparticles in disease diagnosis and treatment. Finally, we discuss the current challenge and future prospective of stimuli‐responsive gold nanoparticles for biomedical applications. This review summarizes recent progress in the development of stimuli‐triggered self‐assembly on gold nanoparticles and introduce the breakthrough of gold nanoparticles in disease diagnosis and treatment. In addition, the current challenge and future prospective of stimuli‐responsive gold nanoparticles for biomedical applications are discussed.